When is a Learning Object not an Object: A first step towards a theory of learning objects - Sosteric, Mike; Hesemeier, Susan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
For some, “learning objects" are the “next big thing” in distance education promising smart learning environments, fantastic economies of scale, and the power to tap into expanding educational markets. While learning objects may be revolutionary in the long term, in the short term, definitional problems and conceptual confusion undermine our ability to understand and critically evaluate the emerging field. This article is an attempt to provide an adequate definition of learning objects by (a) jettisoning useless theoretical links hitherto invoked to theorize learning objects, and (b) reducing the definition of learning objects to the bare essentials. The article closes with suggestions for further research and further refinement of the definition of learning objects.